Using test batteries to evaluate the applied units for students of physical education and sports institutes in Algeria - Mahdi, Azedine (sports creativity, 2025)
There is a growing interest in testing, measurement, and evaluation, which are rapidly developing and playing a significant role in every aspect of human life. People use them in their daily routines, and they have been employed in physical education to develop physical abilities. They have also become a comprehensive assessment tool, allowing for a thorough understanding of their application and concepts. Testing and measurement are crucial factors in establishing and implementing planned programs. They are among the methods that can demonstrate the effectiveness of any program through the use of evaluative tools in various fields.